Acute Renal Failure Secondary to Inadvertent Propylene Glycol Overdose with Single-Day High-Dose Vitamin D (Stosstherapy) - David H. Jelley; Deborah Zayneb Mohamad Ali; Michelle Condren (Case Reports in Endocrinology)
Globally, there has been increasing attention paid to vitamin D deficiency and its treatment. Vitamin D stosstherapy with high-dose ergocalciferol in a single day is reemerging as a potential treatment option. We present an as yet unreported complication of acute renal injury due to propylene glycol toxicity in a 7-month infant treated with vitamin D stosstherapy. The product label for the vitamin D used for this patient states it is dissolved in propylene glycol (PG), but the amount is not listed on this or other US ergocalciferol liquid products that contain PG. Caution should be used when considering vitamin D stosstherapy with liquid ergocalciferol products available in the United States.